UJI ANTAGONIS Trichoderma harzianum TERHADAP Fusarium oxysporum PENYEBAB PENYAKIT LAYU PADA TANAMAN TOMAT (Lycopersicum esculentum) SECARA IN VITRO - Zainuddin Ohorella; Mira Herawati Soekamto; Wahyudi Wahyudi; Muji Hariati (Universitas Muhammadiyah Sorong, 2022)
Fusarium oxysporum is a very harmful fungus because it can attack tomato plants from germination to maturity. Control of fusarium wilt disease, generally only limited to sanitation, biological control by using a biological control agent (APH) Trichoderma harzianum is an alternative to reduce the use of chemical pesticides in disease control. The experiment used a completely randomized design (CRD), with in vitro testing of Trichoderma harzianum against Fusarium oxysporum from stem, leaf, flower and fruit organs of tomato plants. Trichoderma harzianum in in vitro conditions was able to suppress the growth of Fusarium oxysporum which infects fruit by 100%, tomato flower organs 92,2%, tomato leaf organs 59,0% and from tomato plant stem organs 50,2%.